Dalits rights / human rights - Chatterjee, Debi (Rawat Publications, 2016)
Socially stigmatized, culturally subjugated, and politically marginalized, India's Dalits have been the most vulnerable community in terms of human rights violations. This book explores the roots of the vulnerability and the present status of this section of Indian society against the backdrop of the changing social, economic, and political scenario. In particular, it examines the vulnerability of Dalit women, children, and those who are victims of displacement. It also looks into the compulsions under which the Dalits have opted for conversion and their post-conversion status. In covering the negation of their rights and their struggles, the book places the discussion in the wider context of globalization and the unfolding global human rights discourse.